The Mongol World-system and the establishment of the Free Trade Zone in the 13-15th centuries - Kinaiatuly, Zardykhan (The New Research of Tuva, 2009)
The Mongol Empire is a unique phenomenon in the medieval history. The Mongols succeeded to create a truly world empire. Its founder, Chinggis Khan, conquered half of the world, transforming the entire Eurasian steppe system into a coherent political entity with rigid social and political system, strong military organization and postal and communicational network. This empire, which spread from the Pacific Ocean to Eastern Europe and from Siberia to Persia, established its world-system.